2006
DOI: 10.1377/hlthaff.25.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Developing Drugs For Developing Countries

Abstract: Infectious and parasitic diseases create enormous health burdens, but because most of the people suffering from these diseases are poor, little is invested in developing treatments. We propose that developers of treatments for neglected diseases receive a "priority review voucher." The voucher could save an average of one year of U.S. Food and Drug Administration (FDA) review and be sold by the developer to the manufacturer of a blockbuster drug. In a well-functioning market, the voucher would speed access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 23 publications
0
126
0
1
Order By: Relevance
“…One strategy may be to formulate a new regulatory pathway to accelerate novel organ engineering while simultaneously enhancing transparency and post market reporting [21•]. Another strategy may be to expand the priority-review voucher model [22,23], which was established to incentivize industry to develop therapies for neglected diseases. Expanding this incentive to regenerative medicine-based breakthrough therapies such as bioengineering organs could have profound effects.…”
Section: Commercialization Strategies For Enabling Bioengineering Of mentioning
confidence: 99%
“…One strategy may be to formulate a new regulatory pathway to accelerate novel organ engineering while simultaneously enhancing transparency and post market reporting [21•]. Another strategy may be to expand the priority-review voucher model [22,23], which was established to incentivize industry to develop therapies for neglected diseases. Expanding this incentive to regenerative medicine-based breakthrough therapies such as bioengineering organs could have profound effects.…”
Section: Commercialization Strategies For Enabling Bioengineering Of mentioning
confidence: 99%
“…Based on a concept by Ridley, Grabowski, and Moe, 14 in 2007 the US Government created a mechanism by which a pharmaceutical company that gains US Food and Drug Administration (FDA) approval for a new molecular entity "for which there is no significant market in developed nations and that disproportionally affects poor and marginalized populations" is granted a tradable voucher for a priority review by FDA of another drug of its choice. 15 In this case, the voucher granted for the approval of the drug for the developing world would provide a decreased time to market for a highly-profitable drug for the rich world, thus providing a clear financial incentive for the development of the former.…”
Section: Priority Review Voucher (Prv)mentioning
confidence: 99%
“…Finally, it deserves to be mentioned the Priority Review Vouchers (suggested by Ridley et al [11] and later adopted by the Food and Drug Administration of the USA, in the year 2008) that provide incentives to invest in drugs for neglected tropical diseases. Companies that obtain approval for a treatment of a neglected disease are given a transferable voucher that allows them a priority review process for the authorisation of another agent.…”
Section: New Initiatives For Making Drugs More Accessible For Allmentioning
confidence: 99%